Análisis de la evolución del marketing digital de la marca lojana Forestea - Bravo Torres, Diego Alejandro (2020)
This research seeks to analyze the digital marketing strategies of the Forestea brand on the social network Facebook, this brand belongs to the company Induloja, which is dedicated to the marketing of packaged horchata, a traditional beverage from the province of Loja. Santiago Torres, Iván Bermeo and Daniel Torres are the creators of the drink that has become very popular in recent years in the Ecuadorian region. This research work aims to establish whether there is a remarkable evolution in the development of digital marketing for Forestea. This question has been satisfied through the use of scientific and technical methods that contributed to the fulfillment of the objectives set for the present investigation. One of these objectives is based on analyzing each of the company's communication products, on the Facebook social network, including its composition, chromatic factors, typography, message, content, its form of dissemination and interactions by followers of the page. Each of the data obtained has been compiled in observation sheets that helped determine the tools and resources that Forestea uses to strengthen its digital marketing through the social network Facebook. Therefore, and through the records obtained it has been possible to determine that there has been an evolution in digital marketing for the company; However, to further contribute to this process, an alternative proposal has been determined and planned, which seeks to strengthen the credibility of the followers and retain them for the brand.